Modified Turning Vanes in Air Distribution System of HVAC for Thermodynamics Lab - Salahuddin Musa, Saad; Danial Ibrahim, Mohd; Philman Jong, Rudiyanto (International Journal of Engineering and Technology, 2018)
The objective of our study is to develop a new design of turning vanes. We have developed two types of turning vanes, proposed turning vanes 1 and 2 which will then virtually install on thermodynamics laboratory. The result of the simulation was then compared with the conventional turning vanes 1 and 2. It was found that the proposed turning vanes 2 gave better results compared to the conventional turning vanes 2 with improvements of 43.5% in velocity distribution and 16.0% in pressure distribution respectively. The results showed that the best turning vanes was conventional turning vanes. As a conclusion, conventional turning vanes produce better result compared to proposed turning vanes when it virtually applied to the thermodynamics lab. It can be implied that conventional turning vanes produced better outlet velocity compared to the proposed turning vanes. Real experiment should be conducted to verify the numerical result.Â Â